A Bibliometric Analysis of Publication Patterns in Pediatric Neurology - Wilson, Mitch; Sampson, Margaret; Barrowman, Nick; Sucha, Ewa; Doja, Asif (Frontiers in Pediatrics, 2022)
Purpose: To examine the publication patterns of pediatric neurology articles in general pediatric, general neurology, and neurology subspecialty journals using a bibliometric approach. Methods: The top 5 journals in general pediatrics, general neurology and neurology subspecialties were identified using the 2017 Journal Citations Report (JCR). For general pediatric journals, we selected 4 pediatric subspecialties for comparison of publication patterns with neurology: immunology, endocrinology, gastroenterology, and respirology. For general neurology and neurology subspecialty journals, we searched both the top 5 neurology and neurology subspecialty journals for pediatric articles. Using OVID Medline, we identified articles published between 2009-2017. Results: With regards to child neurology-based articles, 1501 were published in general pediatrics journals, 643 in general neurology journals and 685 in neurology subspecialty journals. Examination of the top pediatric journals revealed that Pediatrics published the most neurology-based articles. Neurology-based studies were published more frequently than other pediatric subspecialty studies. Of the top general neurology Neurology published the most child neurology-based articles, while Epilepsia published the most child neurology-based articles out of neurology subspecialty journals. Cohort studies were the most frequent study type across all journals. Conclusions: Our study revealed that child neurology articles are published more often in pediatric journals as opposed to general neurology and neurology subspecialty journals. We also found that in general pediatric journals, neurology-based articles are published more frequently compared to other specialties. Our results provide guidance to authors when considering submission of their pediatric neurology research.